Use of beeswax for papaya preservation as alternative to PVC film (Research, Society and Development, 2024)
To reduce plastic use in the home environment, the "eco-friendly cloth" was developed, made of cotton fabric coated with beeswax as an alternative to PVC film. This study evaluated the impact of this cloth on the preservation of Hawaiian papaya, comparing it to PVC film. Halved papayas were stored in the refrigerator for 10 days and analyzed on days 0, 2, 4, 6, 8, and 10 for weight loss, total soluble solids, pH, color, and appearance. The results showed that although the beeswax cloth was inferior to PVC film in terms of weight loss, it ensured a weight loss of less than 10%. Data on pH, total soluble solids, and color showed no significant differences during storage. In terms of appearance, the treatments did not differ, with both types of packaging maintaining ratings above average until the 10th day. Regarding acceptance, more than 50% of the judges considered the fruits in both packages fit for consumption. After 10 days of storage at 10°C, the beeswax cloth proved to be a viable alternative to PVC film for preserving cut papaya, contributing to the reduction of plastic use.